Pengujian Rusak Untuk Procedure Qualification Record Sambungan Kombinasi Las SMAW-FCAW Pada Material BS EN 10025 S355J2 Berdasarkan Standar AWS D1.1/D1.1M:2020 - Rahman, Gulam Fazlur; Ariyanto, Nugroho Pratomo; Irawan, Benny Haddli (Politeknik Negeri Padang, 2024)
PQR Qualification (Procedure Qualification Record) is an important part of welding. To ensures that the welding procedures used meet the quality requirements of the welding fabrication project. The purpose of this study was to determine the quality of welding and material thickness resistance attest coupon. One way to determine welding qualifications by means of this procedure is to use damage testing which is carried out on the material and welding until it is damaged and meets the set standards. This research will discuss PQR based on the AWS D1.1/D1.1M:2020 standard by requiring two tensile test specimens, two sets of scharpy v-notch (a set of three specimens), four side bend specimens and one macro specimen. The number and type of specimens are set in the AWS D1.1/D1.1M:2020 standard. Results of testing tensile obtained the difference in tensile strength between specimens 1st and 2nd specimens. The value obtained for tensile strength are 508 MPa and 515 MPa with 7 MPa of differences, but these results still with in the limits range of 470 to 630 MPa. Charpy impact testing obtained the results above required value of minimum 27 Joule. The surface bending test of the test specimen did not show any defect as well as in the macro testing. From the results of this tests, the quality of the welding and the thickness of the material can be determined.